2018
DOI: 10.1038/s41467-018-03477-5
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of undecaprenyl-pyrophosphate phosphatase and its role in peptidoglycan biosynthesis

Abstract: As a protective envelope surrounding the bacterial cell, the peptidoglycan sacculus is a site of vulnerability and an antibiotic target. Peptidoglycan components, assembled in the cytoplasm, are shuttled across the membrane in a cycle that uses undecaprenyl-phosphate. A product of peptidoglycan synthesis, undecaprenyl-pyrophosphate, is converted to undecaprenyl-phosphate for reuse in the cycle by the membrane integral pyrophosphatase, BacA. To understand how BacA functions, we determine its crystal structure a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 60 publications
4
60
0
Order By: Relevance
“…BacA represents the other type of C 55 -PP phosphatases, whose structure strongly suggested that the protein might display a C 55 -P flippase activity 7,10 . Such an activity is required to relocalize the C 55 -P product back to the inner side of the membrane to end recycling.…”
Section: Discussionmentioning
confidence: 99%
“…BacA represents the other type of C 55 -PP phosphatases, whose structure strongly suggested that the protein might display a C 55 -P flippase activity 7,10 . Such an activity is required to relocalize the C 55 -P product back to the inner side of the membrane to end recycling.…”
Section: Discussionmentioning
confidence: 99%
“…The successful application of the IMISX method both at room and cryo‐temperatures was demonstrated with seven MPs including two transporters, PepT St and AlgE, four enzymes, DgkA, LspA, PgpB , BacA , and a GPCR, ß 2 AR . For lysozyme, exceptional data quality was obtained from IMISX by sulfur‐SAD phasing using 992 crystals .…”
Section: In Meso In Situ Serial X‐ray Crystallography (Imisx)mentioning
confidence: 99%
“…The cubic phase has also found application as a native-like medium in which to port crystals across beams for time-resolved serial crystallography at synchrotron (Nogly et al, 2015;Weinert et al, 2017) and free-electron laser X-ray sources (Weierstall et al, 2014;White et al, 2016;Nogly et al, 2018;Cheng, 2020). The recently developed in situ in meso serial X-ray crystallography (IMISX) method uses perforated double-stick tape to create wells for crystallization and supporting sachets (IMISX wells) in which to deliver the crystal-laden mesophase to the X-ray beam without the need for direct crystal harvesting (Huang et al, 2015(Huang et al, , 2016(Huang et al, , 2018El Ghachi et al, 2018;Apel et al, 2019;Cheng et al, 2019). The original IMISX method involved securing a slightly curved thin-film sachet to a pin on a goniometer (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…They provide for a wide scanning area and are suitable for post-crystallization treatments such as ligand and heavy-atom soaking (Li et al, 2015;Rucktooa et al, 2018;Huang et al, 2018). The holders can be used with a host of in situ window materials such as cyclic olefin polymer (COP) (Axford et al, 2016;Apel et al, 2019), cyclic olefin copolymer (COC) (Huang et al, 2015(Huang et al, , 2016El Ghachi et al, 2018), biaxially oriented polyethylene terephthalate (Mylar) (Broecker et al, 2016) and silicon nitride (Cherezov & Caffrey, 2007;Murray et al, 2015;Roedig et al, 2015;Owen et al, 2017). Furthermore, the holders are 3D printed and reusable.…”
Section: Introductionmentioning
confidence: 99%